Motivating EFL Learners to Write Using Padlet Application - Syarifuddin Dollah; Muh. Farid Sehuddin; Geminastiti Sakkir (Pascasarjana Universitas Negeri Makassar, 2021)
E- learning is a system or concept of education that utilizes information technology in teaching and learning. One of them is Padlet, which is an internet site that allows people and other users to collaborate on text, photos, links or other content. Each of these collaborative spaces called a “wall” that can be used as a personal bulletin board. Tecahers and companies generally use Padlets to encourage creative multimedia conversation and exchange of opinions. So, this media is expected to be useful for teachers and students in narrative writing learning class. This study is the quasi experimental research that aimed to know the effect and the correlation of the implementation of Padlet to the students’ achievement and motivation in writing. The implementation Padlet as independent variables and the students’ achievement and motivation in writing as a dependent variable. The population in this research is all second grade students in one of senior high school at Makassar that consist of eight classes. One class took as a control group and one class as an experiment group through cluster random sampling technique. The data of the research was obtained by the study results test on the subject of the velocity reaction for pre-test and post-test and questionnaire. Based on analysis of inferential statistics for writing achievement, the P = 0.001, and for motivation, the P = 0,012 and it less than  = 0,05 was obtained, it is means that the implementation Padlet is significantly influence to the students’ motivation and achievement in writing of the second grade senior high school students’ on the material subject of writing.